2015
DOI: 10.4103/0366-6999.155064
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Variability in Vasoactive Agent Therapy

Abstract: Background:Inconsistencies in the use of the vasoactive agent therapy to treat shock are found in previous studies. A descriptive study was proposed to investigate current use of vasoactive agents for patients with shock in Chinese intensive care settings.Methods:A nationwide survey of physicians was conducted from August 17 to December 30, 2012. Physicians were asked to complete a questionnaire which focused on the selection of vasoactive agents, management in the use of vasopressor/inotropic therapy, monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A nationwide survey of Chinese ICUs reported that 70.8% of ICU physicians selected norepinephrine and 27.6% selected dopamine as the first choice of vasopressor for septic shock patients; however, the actual usage level was not clear. [ 13 ] In the same study, dopamine was selected by 73.4% of physicians for hypovolemic shock and 68.3% of physicians for cardiogenic shock as the first-choice vasopressor. Dopamine has previously been recommended as the first choice for cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey of Chinese ICUs reported that 70.8% of ICU physicians selected norepinephrine and 27.6% selected dopamine as the first choice of vasopressor for septic shock patients; however, the actual usage level was not clear. [ 13 ] In the same study, dopamine was selected by 73.4% of physicians for hypovolemic shock and 68.3% of physicians for cardiogenic shock as the first-choice vasopressor. Dopamine has previously been recommended as the first choice for cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup analysis of a randomized controlled trial showed that norepinephrine decreased mortality compared with dopamine in cardiogenic shock, but no difference in mortality was observed in hypovolemic shock [12]. These previous studies comparing norepinephrine and dopamine have investigated patients with sepsis and post-cardiac surgery, based on which, physicians have selected perioperative vasoconstrictors for their patients [15]. Furthermore, studies comparing the effect of norepinephrine and dopamine in noncardiac surgery settings with relatively low mortality are limited [9].…”
Section: Introductionmentioning
confidence: 99%
“…While these agents are commonly used within the ICU to treat circulatory failure, previous studies have shown that heterogeneity in the patient background and variability in physician behavior results in significant variability in their use [12,[15][16][17][18][19]. Information about factors contributing to the variability in physicians' choice of drugs is still scarce.…”
Section: Introductionmentioning
confidence: 99%